Methodology for the digitalization of heritage through interactive technologies and artificial intelligence: Experience with the Residencia de Estudiantes de Madrid in the PLATA project - Conde Melguizo, Rafael; Santín Álvarez, Eva; Alonso Urbano, David (Street Art & Urban Creativity, 2025)
The New Urban Agenda published by UN-Habitat establishes that SDG 11 urges governments to protect the world's urban and natural cultural heritage, setting forth soft measures aimed at culture and education. Among these, it promotes the safeguarding of tangible and intangible cultural heritage, including the use of new technologies, and emphasizes the preservation of local heritage in the face of the current process of global acculturation. Simultaneously, the European Commission’s Recommendation (EU) 2021/1970 states that heritage is a key element in building European identity and encourages Member States to continue their efforts to digitize and preserve Digital Cultural Heritage assets. The PLATA project we present has worked on the creation of a methodology for the digitization of the editorial heritage of Madrid’s Residencia de Estudiantes, incorporating interactive technologies, cloud services, and artificial intelligence into the process.Abstract in English.